Isolation and synthesis of pinocembrin and pinostrobin from Artocarpus odoratissimus [Pemencilan dan sintesis pinocembrin dan pinostrobin dari Artocarpus odoratissimus] - Nyokat, Nyotia; Yen, Khongheng; Hamzah, A. S.; Lim, Isabel Fong; Saaidin, Aimi Suhaili (Malaysian Society of Analytical Sciences, 2017)
Artocarpus odoratissimus is native to Borneo and Mindanao Island. In Sarawak, it is locally known as Terap. Previous studies showed Artocarpus species are rich in phenolic compounds, including flavonoids, stilbenoids and arylbenzofurons. The chemical profile of the indigenous plants from Sarawak, such as A. odoratissimus has not been studied intensively and the analyses of medicinal properties have not been explored. Thus, a phytochemical study is carried out on the root extracts of A. odoratissimus using various chromatographic methods and it has led to the isolation of two known flavonoids, namely pinocembrin (1) and pinostrobin (2). The structures are identified by comparison of their 1H and 13C NMR data with those reported in the literature. Flavonoid molecule incorporated as multifunctional in the pharmaceutical industry. It has a vast range of pharmacological activities, such as antimicrobial, anti-inflammatory, antioxidant, and anticancer activities. Pinocembrin and pinostrobin which are successfully synthesized with 2-hydroxy,4,6-methoxyacetphenone and benzaldehyde as starting materials were discussed.